Penerapan Gaya Kepemimpinan Situasional dalam Menghadapi Perkembangan Teknologi di Pondok Pesantren Tarbiyah Islamiyah Gobah - Hadi Latif; Junaidi Junaidi; Supriadi Supriadi; Arif Septiawan (STIKes Ibnu Sina Ajibarang, 2024)
Leadership within managing an Islamic educational institution must have a situation-based leadership style in the face of technological developments. So from that leadership has a challenge to technological development in the world of education. This research uses descriptive qualitative methods and its type of research is a case study. Data collection techniques include observations, interviews, documents, books, journals, and previous research. The findings of this study are that the application of situational leadership in the houses effectively overcomes the obstacles faced by education in the development of technology using versatile and adaptable strategies. Teachers receive rigorous training and engage in collaborative possibilities, producing enhanced skills and knowledge. As a result, students benefit from more participatory learning techniques, which leads to increased interest and better learning outcomes. Although there are barriers to change and constraints in technological infrastructure, a combination of policy support, external resources, and an inclusive leadership approach effectively addresses these barriers. The overall findings emphasize the importance of situational leadership in overseeing educational innovation and formulating more comprehensive and efficient policies in technological developments.